Предмет: Алгебра, автор: temragalievamalika

срочно на завтра плииз
1) (a + 7)^{2}  + (a - 2)(a + 5) - 7a  \\ 2)(a - 6)^{2}  + (a + 3)(a - 5) + 7 \\ 3) - (a - 3)^{2} + (a + 6)(a - 2) - 8a \\ 4)8 - (a + 5)^{2} (a - 4)(a + 7) + 16a

Ответы

Автор ответа: Reqiuem10
0

Ответ:

Объяснение:

1)(а+7)²+(а-2)(а+5)-7а=а²+14а+49+а²+3а-10-7а= 2а²+10а+39

2)(а-6)²+(а+3)(а-5)+7=а²-12а+36+а²-2а-15+7=2а²-14а+28

3)-(а-3)²+(а+6)(а-2)-8а=-а²+6а-9+а²+4а-12-8а=2а-21

4)8-(а+5)²(а²+3а-28)+16а =8-(а²+10а+25)(а²+3а-28)+16а= 8-(а⁴+3а³-28а²+10а³+30а²-280а+25а²+ 75а-700)+16а= 8-(а⁴+13а³+27а²-205а-700)+16а=8-а⁴-13а³-27а²+221а+700 = -а⁴-13а³-27а²+221а+708

Похожие вопросы